Low-carbon high-freezing-resistance magnesium phosphate cement mortar as well as preparation method and application thereof

By using salt lake lithium extraction waste slag magnesium slag to prepare low-carbon and high-freeze-resistant magnesium phosphate cement mortar, combined with river sand and hydrolyzed silicon alcohol, the problems of high reaction speed and high-cost retarder of magnesium phosphate cement are solved, and low-cost and low-cost retarder are achieved The high frost resistance and water resistance of the carbon footprint are suitable for concrete structure repair.

CN119241201APending Publication Date: 2025-01-03LIAONING PROVINCIAL TRANSPORTATION PLANNING & DESIGN INST +1
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411313186.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The high reaction rate and high cost retarder use of existing magnesium phosphate cement limit its application range in engineering projects, and it has high energy consumption and carbon dioxide emissions during the production process, and the by-product magnesium slag is inactive and difficult to utilize.

Method used

The magnesium slag of salt lake lithium extraction waste slag is prepared by burning, and combined with river sand, hydrolyzed silicon alcohol and mixed water to prepare low-carbon and high-freeze magnesium phosphate cement mortar. The reaction is adjusted through silane coupling agent to control the settling time and Water resistance, reduce the use of retarder.

Benefits of technology

It has achieved high-freeze-resistant magnesium phosphate cement mortar with low cost and low carbon footprint. It has the characteristics of fast hardness and early strength, strong frost resistance and good water resistance. It is suitable for concrete structure repair, reduces construction cycle and maintenance costs, and increases The durability and environmental properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241201A_ABST
    Figure CN119241201A_ABST
Patent Text Reader

Abstract

The invention discloses low-carbon high-freezing-resistance magnesium phosphate cement mortar and a preparation method and application thereof, and belongs to the technical field of constructional engineering materials, the mortar comprises low-carbon magnesium phosphate cement, river sand, hydrolyzed silanol and mixing water; the hydrolyzed silanol is a product obtained by hydrolyzing a silane coupling agent in ethanol and water under an acidic condition; the invention relates to a high-strength concrete, which is prepared from the following formula components in parts by mass: 145 to 250 parts of low-carbon magnesium phosphate cement, 145 to 250 parts of river sand, 7 to 35 parts of silane coupling agent, 42 to 210 parts of ethanol, 21 to 105 parts of water and 10 to 30 parts of water for mixing. The cement has the advantages of adjustable setting time, low carbon, energy conservation, good mechanical properties, strong water resistance and freezing resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building engineering materials and relates to a cement mortar material, in particular to a low-carbon high-freeze-resistant magnesium phosphate cement mortar and a preparation method and application thereof. Background Art

[0002] Magnesium phosphate cement (MPC) is a high-efficiency air-hardening cementitious material, mainly formed by the acid-base reaction of phosphate and magnesium oxide. It has been widely used in the fields of rapid repair of roads, bridges and airport runways due to its rapid solidification, high early strength, excellent bonding properties, cold resistance and wear resistance. It has shown significant advantages in emergency military engineering and airport repair work.

[0003] Since magnesium phosphate cement reacts quickly and often starts to solidify within 30 seconds to 5 minutes, it is usually necessary to add retarders to extend the setting time and ensure the construction quality. However, these retarders, which are mainly composed of boric acid and its salts, account for more than 60% of the total cost of cementitious materials, and are expensive, which seriously limits their application scope in engineering projects. In addition, the process of producing this type of dead-burned magnesium oxide requires high-temperature calcination at 1300 to 1700°C, which not only consumes a lot of energy, but also releases a lot of carbon dioxide, exacerbating environmental pressure. According to research, my country's salt lake brine is rich in lithium resources, accounting for about 80% of the country's total lithium resources. While efficiently recovering lithium, a large amount of boron-containing sintered magnesium oxide will be produced. This by-product is difficult to use because it is almost inactive, but it provides a potential raw material for magnesium phosphate cement, which can not only effectively utilize resources, but also reduce the use of retarders, thereby reducing costs while achieving energy conservation and emission reduction.

[0004] In this context, the patent (application number: 2017104272668, name: a magnesium oxysulfate cement) proposes a method for preparing magnesium oxysulfate cement using magnesium slag from the lithium extraction process. However, this method has not yet explored the durability of its product in depth, and the development of a low-carbon and high-freeze-resistant magnesium phosphate repair mortar with high durability is of great significance for its wide application in various fields. Summary of the invention

[0005] In view of the defects of the prior art, the present invention provides a low-carbon and high-freeze-resistant magnesium phosphate cement mortar and a preparation method and application thereof. The mortar uses boron-containing magnesium oxide prepared by burning magnesium slag from lithium extraction waste from salt lakes as a main raw material, which not only provides a new treatment method for magnesium slag produced by lithium extraction from salt lakes, but also prepares a low-cost, low-carbon and high-freeze-resistant magnesium phosphate cement mortar, which is helpful to promote its application in the field of structural repair.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A low-carbon high-freeze-resistant magnesium phosphate cement mortar comprises low-carbon magnesium phosphate cement, river sand, hydrolyzed silanol and mixing water; the hydrolyzed silanol is a product of hydrolysis of a silane coupling agent in ethanol and water under acidic conditions; the mass parts of each formula component are: 145-250 parts of low-carbon magnesium phosphate cement, 145-250 parts of river sand, 7-35 parts of silane coupling agent, 42-210 parts of ethanol, 21-105 parts of water and 10-30 parts of mixing water.

[0008] To optimize the above technical solutions, the specific measures taken also include:

[0009] Furthermore, the preparation method of the hydrolyzed silanol is: ethanol, water and silane coupling agent are mixed in a mass ratio of 6:3:1, acetic acid is added to adjust the pH value to 3-5, and stirred for 20-60 minutes to obtain hydrolyzed silanol.

[0010] Furthermore, the silane coupling agent is 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane.

[0011] Furthermore, the low carbon magnesium phosphate cement is mixed by the following components in parts by mass: 80 to 100 parts of low carbon magnesium oxide, 45 to 65 parts of phosphate, 15 to 20 parts of retarder and 0 to 100 parts of mineral admixture.

[0012] Furthermore, the low-carbon magnesium oxide is obtained by calcining magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, at a calcination temperature of 800 to 1400° C. for 1 to 5 hours, preferably calcined at 800 to 1100° C. for 3 to 5 hours or calcined at 1100 to 1400° C. for 1 to 3 hours; the phosphate is potassium dihydrogen phosphate and / or ammonium dihydrogen phosphate; the molar ratio of potassium dihydrogen phosphate to ammonium dihydrogen phosphate is 0 to 3:0 to 3, preferably 1:0, 1:1, 1:2, 2:1, 1:3, 3:1, 0:1; the retarder is Any one of boric acid, malonic acid, sulfosalicylic acid, succinic acid, acrylic acid, chloroacetic acid, glutamic acid, serine, arginine, humic acid, acetic anhydride, ammonium acetate, ethyl acetate, barium chloride, barium nitrate, magnesium chloride, aluminum sulfate, sodium silicate and borax, or a mixture of two or more thereof; the mineral admixture is any one of fly ash, blast furnace slag and quartz powder, or a mixture of two or more thereof; the fly ash is Class I fly ash or Class II fly ash; the blast furnace slag is Class S95 ground slag or Class S105 ground slag; the silicon dioxide content of the quartz powder is more than 90%.

[0013] Furthermore, the preparation method of the low carbon magnesium phosphate cement is: each component is separately charged into a ball mill and ball milled to a fineness of 180 to 200 meshes, and then mixed evenly according to a proportion to form a powder; or all components are charged into a ball mill according to a proportion and ball milled to form a powder with a fineness of 180 to 200 meshes.

[0014] Furthermore, the river sand is a mixture of any two or more of river sands having fineness modulus of 3.7-3.1, 3.0-2.3, and 2.2-1.6.

[0015] The present invention also provides a method for preparing the above-mentioned low-carbon and high-freeze-resistant magnesium phosphate cement mortar, comprising the following steps: step 1, mixing low-carbon magnesium phosphate cement and river sand, and stirring evenly; step 2, adding hydrolyzed silanol and mixing water, stirring evenly, to obtain low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0016] The present invention also provides application of the low-carbon and high-freeze-resistant magnesium phosphate cement mortar in rapid repair of building materials.

[0017] To optimize the above technical solutions, the specific measures taken also include:

[0018] Furthermore, surface cracks, spalling and defects of the concrete structure are repaired by pouring, painting, spraying or injecting low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0019] The beneficial effects of the present invention are:

[0020] 1. The raw materials are low-carbon and environmentally friendly. Specifically, the low carbon comes from the fact that no CO2 gas is directly generated during the preparation of sintered magnesium oxide. The raw material is not magnesite, but magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from salt lakes. Only water vapor is discharged during dehydration, which effectively reduces the carbon footprint of the product. By using boron-containing magnesium oxide from sustainable sources, not only environmental pollution is reduced, but also the development of a circular economy is promoted. This environmentally friendly attribute makes the present invention particularly suitable for modern construction and repair projects, meeting the market's growing demand for environmentally friendly building materials.

[0021] Second, fast hardening and early strength, suitable for repairing concrete structures. Specifically, the mortar formula of the present invention has the characteristics of fast hardening and early strength. During the preparation process, phosphate is first dissolved to make the cement slurry weakly acidic, and MgO is dissolved in an acidic environment and releases Mg 2+ , followed by Mg 2+ The complexation reaction with water molecules forms a positively charged "hydrosol"; secondly, the phosphate and MgO react with acid and base. Since the reaction is exothermic, the hydration speed is accelerated, and more and more hydration products are generated, connecting with each other to form a gel. The compressive strength can reach 44.6MPa within 3 hours, which makes it very suitable for repairing concrete structures that need to be quickly restored. The characteristics of rapid hardening and early strength not only shorten the construction period and reduce the impact on traffic during the construction process, but also significantly improve the durability and service life of the repaired concrete structure.

[0022] 3. Strong frost resistance, suitable for road repair in seasonally frozen areas. Specifically, high frost resistance comes from the regulation technology of mortar gas content and pore structure: gas content control is to use the reasonable combination of potassium dihydrogen phosphate and ammonium dihydrogen phosphate to achieve the regulation of MPC mortar gas content. Specifically, the mortar gas content can be controlled between 5% and 9%, while ensuring the mechanical properties, and improving the frost resistance (bonding strength retention rate) of magnesium phosphate repair mortar. This improvement in stability and durability not only ensures the long-term performance of the repaired surface, but also greatly reduces future maintenance needs, saving maintenance costs for users.

[0023] Fourth, it has strong water resistance and effectively improves the durability of magnesium phosphate cement. First, the hydrolyzate of silane coupling agent is a compound containing amino and silanol groups. The amino and silanol groups can interact with magnesium oxide and phosphate in magnesium phosphate cement by physical adsorption, improve the dispersibility and adhesion of the material, thereby adjusting the reaction rate of MgO and phosphate and controlling the setting time. In addition, silane is hydrolyzed and reacted step by step in a mixed solvent composed of water and ethanol to generate silanol groups. The hydroxyl groups on the surface of MgO undergo a dehydration condensation reaction with the silanol groups to achieve the grafting of silane. Finally, dehydration condensation occurs between adjacent silanol groups, thereby enhancing the cohesion of the material and improving the water resistance of magnesium phosphate cement. Finally, acetic acid is used to adjust the pH value of the hydrolysis reaction. Acetic acid can be used as a retarder in magnesium phosphate cement mortar, which relatively reduces the use of other retarders. In particular, the amino group (-NH2) in KH550 reacts with the metal ions (such as Mg) in magnesium phosphate cement. 2+ ) forms a complex, controls the reaction rate of MgO and phosphate, and then controls the setting time and water resistance of magnesium phosphate cement. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD diagram of low carbon magnesium oxide before and after heat treatment at different temperatures;

[0025] Figure 2 It is the microscopic morphology of low carbon magnesium oxide before and after heat treatment at different temperatures;

[0026] Figure 3 This is a photo of the test specimen of low-carbon and high-freeze-resistant magnesium phosphate cement mortar. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific embodiments.

[0028] Example 1

[0029] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0030] Step 1: Pour 145 parts of low-carbon magnesium phosphate cement and 145 parts of river sand with a fineness modulus of 3.7-2.3 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0031] Among them, low-carbon magnesium phosphate cement is prepared from 80 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 800°C for 5 hours), 16 parts of potassium dihydrogen phosphate, 48 parts of ammonium dihydrogen phosphate, 2 parts of malonic acid and 13 parts of borax. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 180 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0032] Step 2: 84 parts of ethanol, 42 parts of water and 14 parts of 3-aminopropyltriethoxysilane are mixed, acetic acid is added to control the pH value to about 3, and stirred for 20 minutes to obtain hydrolyzed silanol. The above hydrolyzed silanol and 15 parts of mixing water are added to the mixture in step 1, and a mixer is used to stir at low speed for 30 seconds and then at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0033] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0034] Example 2

[0035] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0036] Step 1: Pour 165 parts of low-carbon magnesium phosphate cement and 165 parts of river sand with a fineness modulus of 3.7-2.3 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0037] Among them, low-carbon magnesium phosphate cement is prepared from 80 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 1400°C for 2 hours), 32 parts of potassium dihydrogen phosphate, 32 parts of ammonium dihydrogen phosphate, 4 parts of sulfosalicylic acid, 13 parts of borax, 10 parts of fly ash and 10 parts of quartz powder. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 190 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0038] Step 2: Mix 78 parts of ethanol, 39 parts of water and 13 parts of 3-aminopropyltriethoxysilane, add acetic acid to control the pH value to about 3.5, and stir for 25 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 20 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0039] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0040] Example 3

[0041] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0042] Step 1: Pour 185 parts of low-carbon magnesium phosphate cement and 185 parts of river sand with a fineness modulus of 3.7-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0043] Among them, low-carbon magnesium phosphate cement is prepared from 90 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 900°C for 5 hours), 14 parts of potassium dihydrogen phosphate, 42 parts of ammonium dihydrogen phosphate, 4 parts of succinic acid, 16 parts of borax, 30 parts of fly ash and 10 parts of quartz powder. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 200 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0044] Step 2: Mix 42 parts of ethanol, 21 parts of water and 7 parts of 3-aminopropyltrimethoxysilane, add acetic acid to control the pH value to about 3, and stir for 25 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 30 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0045] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0046] Example 4

[0047] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0048] Step 1: Pour 215 parts of low-carbon magnesium phosphate cement and 215 parts of river sand with a fineness modulus of 3.7-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0049] Among them, low-carbon magnesium phosphate cement is prepared from 100 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from salt lakes, is calcined at 1000°C for 4 hours), 17 parts of potassium dihydrogen phosphate, 34 parts of ammonium dihydrogen phosphate, 2 parts of acrylic acid, 13 parts of borax, 15 parts of fly ash, 30 parts of quartz powder and 20 parts of blast furnace slag. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 180 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0050] Step 2: Mix 198 parts of ethanol, 99 parts of water and 33 parts of 3-aminopropyltrimethoxysilane, add acetic acid to control the pH value to about 4, and stir for 35 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 10 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0051] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0052] Example 5

[0053] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0054] Step 1: Pour 250 parts of low-carbon magnesium phosphate cement and 250 parts of river sand with a fineness modulus of 3.7-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0055] Among them, low-carbon magnesium phosphate cement is prepared from 100 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 1100°C for 3 hours), 50 parts of diammonium phosphate, 4 parts of chloroacetic acid, 16 parts of borax, 50 parts of fly ash and 50 parts of quartz powder. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 190 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0056] Step 2: Mix 210 parts of ethanol, 105 parts of water and 35 parts of 3-aminopropyltriethoxysilane, add acetic acid to control the pH value to about 5, and stir for 45 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 15 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0057] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0058] Example 6

[0059] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0060] Step 1: Pour 193 parts of low-carbon magnesium phosphate cement and 193 parts of river sand with a fineness modulus of 3.7-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0061] Among them, low-carbon magnesium phosphate cement is prepared from 100 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 1200°C for 3 hours), 55 parts of potassium dihydrogen phosphate, 1 part of glutamic acid, 14 parts of borax and 38 parts of fly ash. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 200 meshes, and low-carbon magnesium phosphate cement is obtained after mixing.

[0062] Step 2: Mix 42 parts of ethanol, 21 parts of water and 7 parts of 3-aminopropyltriethoxysilane, add acetic acid to control the pH value to about 3, and stir for 45 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 30 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0063] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0064] Example 7

[0065] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0066] Step 1: Pour 223 parts of low-carbon magnesium phosphate cement and 223 parts of river sand with a fineness modulus of 3.0-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0067] Among them, low-carbon magnesium phosphate cement is prepared from 100 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 1300°C for 1.5 hours), 36 parts of potassium dihydrogen phosphate, 18 parts of ammonium dihydrogen phosphate, 4 parts of humic acid, 12 parts of borax and 68 parts of quartz powder. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 180 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0068] Step 2: Mix 150 parts of ethanol, 75 parts of water and 25 parts of 3-aminopropyltrimethoxysilane, add acetic acid to control the pH value to about 4, and stir for 50 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 20 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0069] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0070] Example 8

[0071] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0072] Step 1: Pour 160 parts of low-carbon magnesium phosphate cement and 160 parts of river sand with a fineness modulus of 3.0-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0073] Among them, low-carbon magnesium phosphate cement is prepared from 80 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from salt lakes, is calcined at 800°C for 5 hours), 22 parts of potassium dihydrogen phosphate, 44 parts of ammonium dihydrogen phosphate, 3 parts of acetic anhydride, 13 parts of borax and 15 parts of blast furnace slag. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 190 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0074] Step 2: Mix 72 parts of ethanol, 36 parts of water and 12 parts of 3-aminopropyltrimethoxysilane, add acetic acid to control the pH value to about 3.5, and stir for 60 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 20 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0075] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0076] Example 9

[0077] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0078] Step 1: Pour 185 parts of low-carbon magnesium phosphate cement and 185 parts of river sand with a fineness modulus of 3.7-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0079] Among them, low-carbon magnesium phosphate cement is prepared from 90 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 1400°C for 1 hour), 36 parts of potassium dihydrogen phosphate, 18 parts of ammonium dihydrogen phosphate, 3 parts of ethyl acetate, 16 parts of borax, 10 parts of blast furnace slag and 30 parts of quartz powder. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 200 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0080] Step 2: Mix 90 parts of ethanol, 45 parts of water and 15 parts of 3-aminopropyltriethoxysilane, add acetic acid to control the pH value to about 3.5, and stir for 25 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 22 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0081] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0082] Example 10

[0083] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0084] Step 1: Pour 210 parts of low-carbon magnesium phosphate cement and 210 parts of river sand with a fineness modulus of 3.0-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0085] Among them, low-carbon magnesium phosphate cement is prepared from 100 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 1000°C for 3 hours), 25 parts of potassium dihydrogen phosphate, 25 parts of ammonium dihydrogen phosphate, 3 parts of barium nitrate, 13 parts of borax, 20 parts of fly ash, 20 parts of blast furnace slag and 20 parts of quartz powder. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 180 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0086] Step 2: 150 parts of ethanol, 75 parts of water and 25 parts of 3-aminopropyltriethoxysilane are mixed, acetic acid is added to control the pH value to about 4, and stirred for 45 minutes to obtain hydrolyzed silanol. The above hydrolyzed silanol and 17 parts of mixing water are added to the mixture in step 1, and a mixer is used to stir at low speed for 30 seconds and then at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0087] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0088] Embodiment 11

[0089] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0090] Step 1: Pour 240 parts of low-carbon magnesium phosphate cement and 240 parts of river sand with a fineness modulus of 3.0-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0091] Among them, low-carbon magnesium phosphate cement is prepared from 100 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 1200°C for 2 hours), 36 parts of potassium dihydrogen phosphate, 12 parts of ammonium dihydrogen phosphate, 4 parts of sodium silicate, 13 parts of borax, 55 parts of blast furnace slag and 35 parts of quartz powder. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 190 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0092] Step 2: Mix 180 parts of ethanol, 90 parts of water and 30 parts of 3-aminopropyltriethoxysilane, add acetic acid to control the pH value to about 3, and stir for 20 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 18 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0093] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0094] Example 12

[0095] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0096] Step 1: Pour 190 parts of low-carbon magnesium phosphate cement and 190 parts of river sand with a fineness modulus of 3.7-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0097] Among them, low-carbon magnesium phosphate cement is prepared from 100 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 1000°C for 3 hours), 33 parts of potassium dihydrogen phosphate, 11 parts of ammonium dihydrogen phosphate, 4 parts of aluminum sulfate, 15 parts of citric acid and 35 parts of blast furnace slag. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 200 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0098] Step 2: Mix 48 parts of ethanol, 24 parts of water and 8 parts of 3-aminopropyltrimethoxysilane, add acetic acid to control the pH value to about 3, and stir for 60 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 30 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0099] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0100] Embodiment 13

[0101] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0102] Step 1: Pour 218 parts of low-carbon magnesium phosphate cement and 218 parts of river sand with a fineness modulus of 3.7-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0103] Among them, low-carbon magnesium phosphate cement is prepared from 100 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from salt lakes, is calcined at 900°C for 4 hours), 55 parts of potassium dihydrogen phosphate, 3 parts of glucose, 13 parts of humic acid, 35 parts of blast furnace slag and 28 parts of quartz powder. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 180 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0104] Step 2: 108 parts of ethanol, 54 parts of water and 18 parts of 3-aminopropyltriethoxysilane were mixed, acetic acid was added to control the pH value to about 3, and the mixture was stirred for 30 minutes to obtain hydrolyzed silanol. The above hydrolyzed silanol and 25 parts of mixing water were added to the mixture in step 1, and a mixer was used to stir at low speed for 30 seconds and then at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0105] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0106] Embodiment 14

[0107] This embodiment provides a low-carbon high-freeze-resistant magnesium phosphate cement mortar, and the preparation method comprises the following steps:

[0108] Step 1: Pour 175 parts of low-carbon magnesium phosphate cement and 175 parts of river sand with a fineness modulus of 3.0-1.6 into a mixing container and stir at a low speed for 30 seconds using a mixer.

[0109] Among them, low-carbon magnesium phosphate cement is prepared from 90 parts of low-carbon magnesium oxide (magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, is calcined at 900°C for 3.5 hours), 35 parts of ammonium dihydrogen phosphate, 2 parts of sodium silicate, 18 parts of borax, 10 parts of fly ash, 10 parts of blast furnace slag and 20 parts of quartz powder. The preparation method is: each component is separately loaded into a ball mill and ball milled for 15 minutes to obtain a uniform powder with a fineness of 190 mesh, and low-carbon magnesium phosphate cement is obtained after mixing.

[0110] Step 2: Mix 90 parts of ethanol, 45 parts of water and 15 parts of 3-aminopropyltrimethoxysilane, add acetic acid to control the pH value to about 5, and stir for 50 minutes to obtain hydrolyzed silanol. Add the above hydrolyzed silanol and 20 parts of mixing water to the mixture in step 1, use a mixer to stir at low speed for 30 seconds and then stir at high speed for 90 seconds to prepare a uniform low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0111] The peeling layer of the concrete pavement was repaired by brushing with low-carbon and high-freeze-resistant magnesium phosphate cement mortar, and after the repair, a 3.5wt% sodium chloride solution was used to perform freeze-thaw cycle damage.

[0112] The properties of the low-carbon and high-freeze-resistant magnesium phosphate cement mortars prepared in Examples 1 to 14 are shown in Table 1.

[0113] Table 1 Performance of low carbon high frost resistance magnesium phosphate cement mortar of Examples 1 to 14

[0114]

[0115] Table 2 Bubble structure parameters of low carbon and high frost resistance magnesium phosphate cement mortar with different ratios of potassium dihydrogen phosphate to ammonium dihydrogen phosphate

[0116]

[0117]

[0118] By comparing the various embodiments, it can be seen that the low-carbon high-freeze-resistant magnesium phosphate cement mortar is prepared by using low-carbon magnesium oxide produced by calcining magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from salt lakes, and its bonding strength grade can reach 5.4MPa or above, wherein the total amount of mineral powder is 35-60 parts, and the calcination temperature of magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from salt lakes, is 900-1300°C. When the mechanical properties of the mortar are optimal, the bonding strength can reach 6.9MPa, and the setting time and fluidity can be adjusted, which meets the technical requirements of strength grade in JC / T 2537-2019 "Magnesium Phosphate Repair Mortar". This low-carbon high-freeze-resistant magnesium phosphate cement mortar can greatly improve the utilization efficiency of magnesium slag extracted from salt lakes, improve the production efficiency of magnesium phosphate cement products, improve the quality of products, reduce their production costs, and reduce pollution to the environment. At the same time, when the mass ratio of potassium dihydrogen phosphate to ammonium dihydrogen phosphate is 1:1, 1:2 and 2:1, the air content is between 5% and 9% and the bubble spacing is less than 250 microns. After 50 freeze-thaw cycles, the retention rate of the bonding strength is above 75%, indicating that the low-carbon and high-freeze-resistant magnesium phosphate cement mortar has good frost resistance and is suitable for cold areas. In addition, by comparison, it can be found that when the addition amount of silane coupling agent is 25 to 35 parts, the water absorption rate of magnesium phosphate cement mortar components can be reduced to 39%, indicating that hydrolyzed silanol can effectively improve the durability of low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

[0119] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields.

[0120] It should be noted that the terms such as "upper", "lower", "left", "right", "front", "back", etc. cited in the invention are only for the convenience of description and are not used to limit the scope of implementation of the present invention. Changes or adjustments in their relative relationships should be regarded as the scope of implementation of the present invention without substantially changing the technical content.

[0121] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A low-carbon and high-freeze-resistant magnesium phosphate cement mortar, characterized in that: It includes low carbon magnesium phosphate cement, river sand, hydrolyzed silanol and mixing water; The hydrolyzed silanol is a product of the hydrolysis of a silane coupling agent in ethanol and water under acidic conditions; The mass proportions of the various formula components are: 145-250 parts of low-carbon magnesium phosphate cement, 145-250 parts of river sand, 7-35 parts of silane coupling agent, 42-210 parts of ethanol, 21-105 parts of water and 10-30 parts of mixing water.

2. The low-carbon and high-freeze-resistant magnesium phosphate cement mortar according to claim 1, characterized in that: The preparation method of the hydrolyzed silanol is as follows: ethanol, water and a silane coupling agent are mixed in a mass ratio of 6:3:1, acetic acid is added to adjust the pH value to 3-5, and the mixture is stirred for 20-60 minutes to obtain the hydrolyzed silanol.

3. The low-carbon and high-freeze-resistant magnesium phosphate cement mortar according to claim 1 is characterized in that: The silane coupling agent is 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane.

4. The low-carbon and high-freeze-resistant magnesium phosphate cement mortar according to claim 1, characterized in that: The low-carbon magnesium phosphate cement is prepared by mixing the following components in parts by mass: 80 to 100 parts of low-carbon magnesium oxide, 45 to 65 parts of phosphate, 15 to 20 parts of retarder and 0 to 100 parts of mineral admixture.

5. The low-carbon and high-freeze-resistant magnesium phosphate cement mortar according to claim 4 is characterized in that: The low-carbon magnesium oxide is obtained by calcining magnesium hydroxide, an intermediate product in the process of extracting lithium carbonate from a salt lake, at a calcination temperature of 800 to 1400° C. and a calcination time of 1 to 5 hours; The phosphate is potassium dihydrogen phosphate and / or ammonium dihydrogen phosphate; the molar ratio of potassium dihydrogen phosphate to ammonium dihydrogen phosphate is 0-3:0-3; The retarder is any one of boric acid, malonic acid, sulfosalicylic acid, succinic acid, acrylic acid, chloroacetic acid, glutamic acid, serine, arginine, humic acid, acetic anhydride, ammonium acetate, ethyl acetate, barium chloride, barium nitrate, magnesium chloride, aluminum sulfate, sodium silicate, and borax, or a mixture of two or more thereof; The mineral admixture is any one of fly ash, blast furnace slag, and quartz powder or a mixture of two or more thereof; the fly ash is Class I fly ash or Class II fly ash; the blast furnace slag is Class S95 ground slag or Class S105 ground slag; and the silicon dioxide content of the quartz powder is more than 90%.

6. The low-carbon and high-freeze-resistant magnesium phosphate cement mortar according to claim 4, characterized in that: The preparation method of the low carbon magnesium phosphate cement comprises: respectively putting each component into a ball mill for ball milling to a fineness of 180-200 meshes, and then mixing them uniformly according to a proportion to form a powder; or putting all the components into a ball mill according to a proportion to ball mill to form a powder with a fineness of 180-200 meshes.

7. The low-carbon and high-freeze-resistant magnesium phosphate cement mortar according to claim 1, characterized in that: The river sand is a mixture of any two or more of river sands having fineness modulus of 3.7-3.1, 3.0-2.3, and 2.2-1.

6.

8. The method for preparing the low-carbon and high-freeze-resistant magnesium phosphate cement mortar according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Mix low carbon magnesium phosphate cement and river sand and stir evenly; Step 2: Add hydrolyzed silanol and mixing water, stir evenly to obtain low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

9. Use of the low-carbon, high-freeze-resistant magnesium phosphate cement mortar as claimed in claim 1 in rapid repair of building materials.

10. Application of the low-carbon and high-freeze-resistant magnesium phosphate cement mortar according to claim 9 in rapid repair of building materials, characterized in that: The surface cracks, spalling and defects of concrete structures are repaired by pouring, painting, spraying or injecting low-carbon and high-freeze-resistant magnesium phosphate cement mortar.

Citation Information

Cited By

  • Method for preparing modified regenerated magnesium oxide and magnesium phosphate cement from magnesium-containing waste

    CN119976903A

  • Method for preparing modified regenerated magnesium oxide and magnesium phosphate cement by using magnesium-containing waste

    CN119976903B

  • Magnesium phosphate fire-resistant composite coating based on industrial solid waste and preparation method of magnesium phosphate fire-resistant composite coating

    CN120574494A

  • A magnesium phosphate fire-resistant composite coating based on industrial solid waste and a preparation method thereof

    CN120574494B

  • Salting-out modified polymer-based magnesium phosphate cement repair material for airfield pavement and preparation method of salting-out modified polymer-based magnesium phosphate cement repair material

    CN122233751A